Pengaruh Citra Merek dan Persepsi Harga Terhadap Keputusan Pembelian (Studi Kasus Sarung Khas Balige) - Pakpahan, Desi Anju Nadetha; Simanjuntak, Mariana (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research was aimed to find out the influence of brand image and price perception on purchasing decisions. This research used quantitative methods with the typical Balige Sarong business object. In this research, the independent variables were brand image and price perception, while the dependent variable is purchasing decisions. The population of this research was the entire Balige community. Samples were taken from the population using Non-Probability Sampling techniques with Accidental Sampling techniques. This research has a target sample of 100 business actors (distributors and retailers) and buyers of Khas Balige sarongs. The research instrument used to collect data was a Likert scale questionnaire. The instrument was tested using SPSS Amos 26. The data analysis method used in this research was multiple linear regression analysis and hypothesis testing (t-test). The research results showed that there was a high influence on brand image and price perception and purchasing decisions by 93%. Each independent variable also influences the dependent variable. Brand image has a positive and significant effect on purchasing decisions. This was indicated by the Critical Ratio (CR) value of 3.149 with probability = 0.002 < 0.005. Price perception has a positive and significant effect on purchasing decisions. This was indicated by the Critical Ratio (CR) value of 2.959 with probability = 0.003 < 0.005.